Pelatihan Kemampuan Guru Pendidikan Agama Kristen dalam Penggunaan Teknologi Media Pembelajaran untuk Meningkatkan Minat Belajar Siswa di PAUD Filadelfia Oefkeun - Juliana Pontoan; Yoksan E. Neno (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2026)
This Community Service activity aims to train the ability of Christian Religious Education (PAK) teachers in Early Childhood Education (PAUD) in using learning media technology to increase student interest in learning. PAK teachers in PAUD have an important role in introducing and instilling Christian values that strengthen children's faith and character from an early age. The use of learning media technology can help PAK teachers deliver material in an interactive and interesting way, so as to increase students' interest in learning. However, many PAK teachers in PAUD still experience limitations in utilizing learning media technology due to lack of skills and access to training. This community service activity focuses on helping teachers overcome these obstacles by conducting training on PAK teachers' ability to use learning media technology that is interesting and aligned with Christian values to support a more effective teaching process. The purpose of this PkM is to increase knowledge about learning media technology, skills in teaching using learning media technology and developing the ability of PAK teachers to present more interactive, varied and interesting learning so that student interest in learning can increase. This PkM activity uses an approach that includes a survey to identify the needs and constraints of teachers, training through seminars to provide a theoretical foundation and practice through workshops with guidelines for making teaching materials containing Christian values using power point learning media technology. This activity was attended by 8 teachers from FILADELFIA OEFKEUN PAUD and 14 people from PkM members who participated in seminars and workshops. The results of this PkM activity are PAUD teachers understand and use learning media technology, especially power point as one of the tools to create interactive and interesting learning materials so that children learn with enthusiasm and fun